Impact of extended-release niacin on immune activation in HIV-infected immunological non-responders on effective antiretroviral therapy. Issue 6 (23rd December 2020) - Lebouché, Bertrand; Yero, Alexis; Shi, Tao; Farnos, Omar; Singer, Joel; Kema, Ido; Costiniuk, Cecilia T.; Thomas, Réjean; Brouillette, Marie-Josée; Engler, Kim; Routy, Jean-Pierre; Jenabian, Mohammad-Ali; et al.
Abstract : Background: Background: Tryptophan (Trp) catabolism into immunosuppressive kynurenine (Kyn) is involved in immune dysregulation during HIV infection. Niacin (vitamin B3) could control the excess of tryptophan depletion and represents a potential strategy to improve immune functions and CD4 count recovery in immunological non-responder HIV-infected individuals on antiretroviral therapy (ART). Methods: Methods: In the CTN PT006 phase 2 pilot randomized trial, 20 adults on ART with CD4 ≤ 350 cells/µl, despite an undetectable viral load (VL) for at least 3 months, received 2000 mg of extended-release (ER)-niacin orally once daily for 24 weeks. Side effects, VL, CD4/CD8 counts, lipid profile, T-cell activation and senescence, Tregs and Th17 cell frequencies, Kyn/Trp ratio, and levels of IL-6, IP-10, sST2, I-FABP, and LBP were assessed following ER-niacin treatment. Results: Results: Thirteen participants completed the study. Treatment was interrupted in 4 patients due to loss of follow-up or personal reasons and 3 patients were discontinued due to comorbidity risks. All participants maintained a VL < 40 copies/ml, while ER-niacin did not affect CD4 and CD8 cell counts. Plasma levels of triglycerides, total, and LDL cholesterol significantly decreased, following ER-niacin treatment. ER-niacin also diminished Kyn plasma levels and slightly decreased CD4 T-cell activation. However, no improvement in CD8 subsets, Kyn/Trp ratio, Th17/Treg balance, and plasma inflammatory markers was observed. Conclusions: Conclusions: Although ER-niacin combined with ART was well-tolerated among immune non-responders and decreased plasma lipids, it did not improve systemic inflammation, Kyn/Trp ratio, and CD4 cell recovery. Overall, ER-niacin was not effective to overcome chronic inflammation in PLWH.